CSCoupons - applying context-sensitivity to increase fast food advertising usefulness - Falcão, Rodrigo; Vieira, Vaninha (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
Companies spend too much money on advertising in order to improve their sales. However, the ratio between investment and effective sales is low. Increasing the usefulness of provided ads and discount coupons is an ongoing challenge in advertising, in order to enhance return on investments, reducing wastage and increasing revenue. Ubiquitous computing offers many features that are considered compliant to advertising needs. A key aspect in ubiquitous computing is the use of context information to provide information more relevant to users, according to their current situation and environment. This paper introduces CSCoupons, a mobile context-sensitive system to deliver discount coupons. We conduct an experiment with a developed prototype of CSCoupons to assess the ideas about fast food coupons in shopping malls. To measure the utility rate of delivered discount coupons, we compared two versions of the prototype: with and without considering context information. The preliminary results show context-sensitivity highly increases advertising usefulness.